CCNA security study guide : exam 210-260 - McMillan, Troy (Indianapolis, Indiana : Sybex, a Wiley Brand, 2018)
"Comprehensive preparation for Exam 210-260, with expert coverage of all exam objectives and a robust tool kit of learning aids. Providing explanation and insight into the installation, troubleshooting, and monitoring of secure networks, this guide helps candidates develop the technological competency they need to maintain the integrity, confidentiality, and availability of data and devices. Practical examples give you a real-world understanding of critical security issues, and access to the Sybex online interactive learning environment provides chapter tests, electronic flashcards, practice exams, and more to help you maximize your study time while building skills and confidence."--Page 4 of cover
Understanding Security Fundamentals -- Understanding Security Threats -- Understanding Cryptography -- Securing the Routing Process -- Understanding Layer 2 Attacks -- Preventing Layer 2 Attacks -- VLAN Security -- Securing Management Traffic -- Understanding 802.1x and AAA -- Securing a BYOD Initiative -- Understanding VPNs -- Configuring VPNs -- Understanding Firewalls -- Configuring NAT and Zone-Based Firewalls -- Configuring the Firewall on an ASA -- Intrusion Prevention -- Content and Endpoint Security -- Comprehensive Online Learning Environment.
Online resource; title from PDF title page (EBSCO, viewed January, 12, 2018).
John Wiley and Sons
Keywords: Cisco IOS; Cisco IOS; Routing (Computer network management) -- Examinations -- Study guides; Telecommunication -- Switching systems -- Examinations -- Study guides; Telecommunications engineers -- Certification; Computer networks -- Security measures -- Examinations -- Study guides; x; x -- Examens; x -- Mesures -- Examens; COMPUTERS -- Security -- Online Safety & Privacy; COMPUTERS -- Security -- Networking; COMPUTERS -- Security -- General; Computer networks -- Security measures -- Examinations; Telecommunication -- Switching systems -- Examinations; Telecommunications engineers -- Certification; examination study guides; Study guides; Study guides; 2